A manganese-based coordination polymer; synthesis, structure and catalytic activity. (1st July 2016) - Alghool, Samir; Slebodnick, Carla; Khaled, Khaled
A two-dimensional manganese(II)-based coordination polymer [Mn(L)4(CH3COO)2] [L=1, 4-bis(1-imidazolyl)benzene] has been synthesised. Its X-ray structure revealed that the layers of the 2D structure are stacked together by two types of weak interactions extending to form a three-dimensional supramolecular structure. The thermal stability of this coordination polymer is described and the compound has been used as a heterogeneous catalyst in oxidation of cyclohexene to cyclohexene oxide. A density functional study of structural parameters, position of the HOMO and LUMO energies, electrophilicity and global hardness is reported.